neo-Clerodane diterpenoids from Salvia dugesii and their bioactive studies - Gang, Xu (Springer Berlin Heidelberg, 2011)
Salvia dugesii is an invasive plant in Yunnan, China. To tentatively explore its utilization, a systematic phytochemical investigation was carried out on this plant, which led to the isolation of five new neo-clerodane diterpenoids, dugesins C–G (1–5), together with six known ones. Their structures were determined by comprehensive NMR and MS spectroscopic analysis. It was noteworthy that the eleven isolates, composed of five different carbocyclic systems derived from the neo-clerodane diterpenoid skeleton, were reported from the same plant for the first time. The anti-feedantial, cytotoxic, and antiviral activities of the isolates were evaluated. Dugesin F (4) was tested to be a non-toxic antiviral compound against influenza virus FM1. [Image: see text] ELECTRONIC SUPPLEMENTARY MATERIAL: Supplementary material is available for this article at 10.1007/s13659-011-0016-6 and is accessible for authorized users.